2013
DOI: 10.1073/pnas.1215353110
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and rheology of a flow-induced structured phase in wormlike micellar solutions

Abstract: Surfactant molecules can self-assemble into various morphologies under proper combinations of ionic strength, temperature, and flow conditions. At equilibrium, wormlike micelles can transition from entangled to branched and multiconnected structures with increasing salt concentration. Under certain flow conditions, micellar structural transitions follow different trajectories. In this work, we consider the flow of two semidilute wormlike micellar solutions through microposts, focusing on their microstructural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
56
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 62 publications
(122 reference statements)
10
56
1
Order By: Relevance
“…Since semidilute micellar solutions usually possess weak viscoelasticity, they are more desirable for oil recovery and encapsulation related applications with higher mobility. Moreover, cationic surfactant solutions with organic salts in the semidilute regime have shown not only interesting rheological behaviors [Ouchi et al (2007); Shikata et al (1987); Vasudevan et al (2008)] but also exhibited unique capabilities in forming irreversible nanostructured phases [Cardiel et al (2013);Cardiel et al (2014b); Dubash et al (2011);Vasudevan et al (2010)] for encapsulation and sensing applications [Cardiel et al (2014a); Lu et al (2010)]. Motivated by the temperature sensitive nature of SHNC and the advantage of semidilute wormlike micellar solutions, this work focuses on the rheological behavior of aqueous CTAB/SHNC mixtures in the semidilute regime, in which micelles are positively charged and isotropically distributed.…”
Section: Introductionmentioning
confidence: 99%
“…Since semidilute micellar solutions usually possess weak viscoelasticity, they are more desirable for oil recovery and encapsulation related applications with higher mobility. Moreover, cationic surfactant solutions with organic salts in the semidilute regime have shown not only interesting rheological behaviors [Ouchi et al (2007); Shikata et al (1987); Vasudevan et al (2008)] but also exhibited unique capabilities in forming irreversible nanostructured phases [Cardiel et al (2013);Cardiel et al (2014b); Dubash et al (2011);Vasudevan et al (2010)] for encapsulation and sensing applications [Cardiel et al (2014a); Lu et al (2010)]. Motivated by the temperature sensitive nature of SHNC and the advantage of semidilute wormlike micellar solutions, this work focuses on the rheological behavior of aqueous CTAB/SHNC mixtures in the semidilute regime, in which micelles are positively charged and isotropically distributed.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been known that the emerging superstructures can range from spherical and elongated cylindrical to very long, flexible wormlike micelles with or without branches [1][2][3][4][5][6][7][8][9] and topologically rich knotted structures [7,8]. The diversity in microstructure and rheological properties make micellar solutions beneficial to numerous applications [10] as hydrofracking fluids in oil industry, turbulent friction drag reducing agents [8], thickening agents in consumer products, drug carriers in targeted delivery [11], and templates to create functional nanofluids with tunable mechanical or optical properties [12][13][14].…”
mentioning
confidence: 99%
“…This irreversible gelation originates from a combination of the high rates of strain (_ $ 5000 s À1 ) and from the extensional characteristics of the flow. Cardiel et al [26] extended this study and reported the formation of FISP from both ionic shear thinning and shear thickening micellar solutions when subjected to strain rates $ 10 3 s À1 and strains $ 10 3 . The FISP consists of entangled, branched, and multiconnected micellar bundles, evidenced by electron microscopy imaging.…”
Section: Introductionmentioning
confidence: 87%
“…The smaller gap size (higher shear rates) in the micropost array can facilitate scaffold formation with smaller pore sizes, therefore enhancing the connectivity of SWCNTs in the FISP-SWCNTs. However, we only employed the flow rate of 15 lm in this work to keep the experimental conditions consistent with our previous work to form plain FISP [26] for comparison purposes. The gap size between the micropost arrays was maintained at $15 lm with height $75 lm.…”
Section: Electro-conductive Porous Scaffold Synthesismentioning
confidence: 93%